Dental caries in primary and permanent molars in 7-8-year-old schoolchildren evaluated with Caries Assessment Spectrum and Treatment (CAST) index - Baginska, Joanna (BioMed Central, 2014)
BACKGROUND: No reports on a caries pattern covering the full spectrum of the disease could be found in the literature. The aim of this study was to evaluate caries in primary and first permanent molars of 7-8-year-old Polish children by the Caries Assessment Spectrum and Treatment (CAST) index and to find whether there was any correlation between the caries stages in such teeth. METHODS: The study covered 284 7-8-year-old children from randomly selected schools in the Bialystok District, Poland. The prevalence of CAST categories was evaluated with regard to the first and second primary, and first permanent, molars. The Spearman’s rank correlation coefficient was used to explore the correlation of the distribution of CAST codes among the evaluated teeth. The level of statistical significance was established at p < 0.05. The intra-examiner reliability was determined by the unweighted kappa coefficient. RESULTS: With regard to the permanent molars, caries was observed in 14.8% to 17.3% of the molar and most lesions were scored at the non-cavitation level. Caries in primary molars was most often recorded at the stage of cavitated dentine lesion. Teeth with pulpal involvement, sepsis and extracted due to caries were found to be more prevalent in first, and then in second primary molars. A strong correlation was found between the status of teeth from the right and left sides of the oral cavity. The correlation of the status of first and second primary teeth was stronger for the left than for the right side of the mouth, r was 0.627 and 0.472 in maxilla and 0.513 and 0.483 in mandible (p < 0.001), respectively. For the neighbouring primary and permanent molars the correlation was assessed to be weak. With regard to the teeth situated in opposite jaws the study revealed that the correlations were moderate - r between 0.33 and 0.49. The intra-examiner reliability was established at 0.96 for the primary dentition and at 0.878 for permanent molars. CONCLUSION: The strongest correlation found in the evaluated population concerned the distribution of caries in primary molars on the left side of the mouth. The study proved the usefulness of the CAST index in epidemiological surveys.